Modeling phosphorus in rivers at the global scale: recent successes, remaining challenges, and near-term opportunities - Harrison, John A.; Beusen, Arthur HW; Fink, Gabriel; Tang, Ting; Strokal, Maryna; Bouwman, Alexander F.; Metson, Geneviève S.; Vilmin, Lauriane (Elsevier BV, 2019)
Understanding and mitigating the effects of phosphorus (P) overenrichment of waters globally, including the evaluation of the global Sustainability Development Goals, requires the use of global models. Such models quantitatively link land use, global population growth and climate to aquatic nutrient loading and biogeochemical cycling. Here we describe, compare, and contrast the existing global models capable of predicting P transport by rivers at a global scale. We highlight important insights gained from the development and application of these models, and identify important near-term opportunities for model improvements as well as additional insight to be gained through new model analysis.
Keywords: Taverne; General Environmental Science; General Social Sciences; SDG 13 - Climate Action; SDG 15 - Life on Land